The Use of Dental Sealing in Cluj, Romania: Frequency, Materials and Techniques – A Questionnaire Study - CORNEA, DANIELA (Clujul Med, 2014)
AIMS. Dental decay is a condition that affects both temporary and permanent dentitions. Prophylactic methods for dental decays consist of: dental sealing, use of fluorides, oral hygiene and healthy diet habits. This article focuses on the frequency, dental materials and techniques of dental sealing used for caries prophylaxis in the Cluj County. MATERIALS AND METHODS. The study used a set of questionnaires that was applied to 175 doctors/dentists from Cluj. The questionnaire contained 11 questions and was delivered to the doctors personally or by the internet RESULTS. From the interviewed dentists 85.7% use dental sealing and 86.7% use materials based on composite resins in this respect. For diagnostic purposes,76% of the dentists use inspection and palpation, 68.66% use cotton rolls and aspiration for isolation, 74% use professional brushing, 74% call back the patient after 6 months for a check-up and 60% of the doctors redo the sealing if the sealant is partially or entirely lost or they perform a filling if a secondary decay appeared. CONCLUSIONS. Most of the interviewed dentists perform dental sealing and consider it as a good caries prophylaxis method. Also, most of them use a material based on composite resins as pit and fissure sealant. The techniques for this procedure are different among the interviewed dentists.